Designing The Utilization of E-learning in Primary School Post COVID-19 Pandemic - Lestari, Puji; Machmudah, Fajriyatul (Universitas Muhammadiyah Ponorogo, 2023)
Gradually, the COVID-19 pandemic starts to dissipate. The field of education has started to reimplement face-to-face education. This caused e-learning based lessons to be abandoned. The way the students study and the learning process have changed. This condition brought the continuation of education to the e-learning era as a facility. Combining information and communication technology appropriately is an important issue in designing a good e-learning. This research is a descriptive qualitative research. The employed data collection techniques are library research methods with procedures for collecting data sources that discuss the explanation, benefits, and advantages of education using e-learning. The findings is the learning plan utilizing e-learning which refers to the concept of e-learning on the four learning setting quadrants by Noord, two continuums of learning strategy by Smaldino et al., and four standards of learning process by Chaeruman, with five processes which are; 1) Determining Learning Competencies; 2) Learning Setting; 3) Standards of learning process; 4) Learning strategy; 5) The Usage of LMS in learning.